A Canadian Survey on Adverse Symptoms Experienced by Solid Organ Transplant Recipients. (September 2020) - Aladwan, Shirin; Harrison, Jennifer J.; Blackburn, David F.; Taylor, Jeff; Blydt-Hansen, Tom D.; Mansell, Holly
Introduction: Adverse symptoms experienced by solid organ transplant recipients remain largely unexplored despite their purported frequency. Objective: To characterize patient perspectives on adverse symptoms, identifying the most problematic symptoms and the perceived cause and treatability, and to evaluate their impact on quality of life (QoL) and medication adherence. Methods: An electronic survey was distributed to members of the Canadian Transplant Association, to characterize perceptions on symptom experience (Modified Transplant Symptom Occurrence and Distress Scale), and QoL (Short Form-12), medication adherence (Basel Assessment of Adherence to Immunosuppressive Medications Scale), demographics, and clinical situation. Results: The questionnaire was distributed to 249 solid organ transplant recipients and achieved a 51% response rate (N = 127). Respondents reported a mean of 25 (standard deviation 10) adverse symptoms each. In women, the most prevalent and distressing symptoms were tiredness, lack of energy, sleep difficulties, difficulty concentrating or memory problems, diarrhea, joint pain, and depression. In men, they were tiredness, flatulence, lack of energy, sleep difficulties, and erectile problems. With the exception of flatulence, these symptoms were more often perceived to be caused by medical conditions rather than by immunosuppressants or other medications. Quality of life was similar to the general public, with mean physical and mental component scores of 47.4 (9.9) and 52.1 (8.2), respectively (relative to a US average of 50 [10]). However, QoL scores inversely correlated to the number of symptoms reported and were higher in patients who perceived all symptoms to be treatable. Conclusion: Adverse symptoms may impact patient well-being. Perceived cause and treatability should be further explored.